(untitled) (Bangladesh Journal of Medical Science, 2017)
In some cases a combination of several malignant tumours in one person can be observed. In such case it is the multifocal primary tumour (MPT). The tumours combination in genitourinary system is rare phenomenon, including a rare combination of prostate and urinary bladder cancers. These pathologies can be caused by both the endogenous factors - age, gender, heredity, inflammatory and proliferative processes, abnormal inclusions (calculi and amyloids) and exogenous factors, among which the leading cause is the environmental pollution (heavy metals salts and others), bad habits, occupational hazards, oncogenic viruses and ionizing radiation. A 76 - year- old male patient, Ukrainian, was hospitalized at urology department with complaints on pollakiuria, frequent urinary retention, haematuria appeared about 1 month before. After examination of patient the preliminary diagnosis was made: «Urinary bladder cancer, acute urinary retention, macrohematuria and posthemorrhagic anemia». Based on the histological and immunohistochemical examinations, the final diagnosis was determined: combined malignant tumours - acinar adenocarcinoma of prostate index 9 (5 + 4) accordimg to D.F. Gleason and invasive urothelial carcinoma of the urinary bladder. This clinical case demonstrates that the probability of combined oncologic cancer pathology with lesions in one system is rather high. Therefore, in order to exclude the cancer combinations, the patients with malignant tumour in the genitourinary system should undergo a complex examination. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.161-165